A novel stepwise approach incorporating ethanol infusion in the vein of Marshall for the ablation of persistent atrial fibrillation - Sousonis, Vasileios; Combes, Stéphane; Pinon, Pauline; Combes, Nicolas; Cardin, Christelle; Zeriouh, Sarah; Menè, Roberto; Jacob, Sophie; Boveda, Serge; Albenque, Jean Paul (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Apart from pulmonary vein isolation (PVI), several step-by-step procedures that aim to modify left atrial substrate have been proposed for the ablation of persistent atrial fibrillation (AF), yet the optimal strategy remains elusive. There are cumulative data suggesting an incremental benefit of adding vein of Marshall (VOM) ethanol infusion to PVI in patients with persistent AF. We sought to evaluate the feasibility and efficacy of a novel stepwise ablation approach, incorporating a VOM alcoholization step, for persistent AF. Methods: In this single-center study, we prospectively enrolled 66 consecutive patients with symptomatic persistent AF and failure of at least one antiarrhythmic drug (ADD). The ablation procedure consisted of i) PVI, ii) left atrial segmentation with VOM ethanol infusion and the deployment of linear radiofrequency lesions across the roof and the mitral isthmus and iii) electrogram-based ablation of dispersion zones. The first two steps were performed in all patients, whereas the third step was carried out only in those still in AF at the end of the second step. Atrial tachycardias during the procedure were mapped and ablated. At the end of the procedure, cavotricuspid isthmus ablation was additionally performed in all patients. The primary endpoint was 12-month freedom from AF and atrial tachycardia after a single procedure and an initial three-month blanking period. Results: Total procedure time was 153±38.5 minutes. Fluoroscopy time was 16±6.5 minutes and the radiofrequency ablation time was 26.14±0.26 minutes. The primary endpoint occurred in 54 patients (82%). At 12 months, 65% of patients were off any AAD. In the univariate Cox regression analysis, only a left ventricular ejection fraction <40% was a predictor of arrhythmia recurrence (HR 3.56; 95% CI, 1.04-12.19; p=0.04). One patient developed a pericardial tamponade and another a minor groin hematoma. Conclusion: A novel stepwise approach, including a step of ethanol infusion in the VOM, is feasible, safe and provides a high rate of sinus rhythm maintenance at 12 months in patients with persistent AF.